Effects of exogenous methyl jasmonate on the synthesis of endogenous jasmonates and the regulation of photosynthesis in citrus. Issue 3 (3rd September 2020) - Qiu, Xia; Xu, Yinghuan; Xiong, Bo; Dai, Lin; Huang, Shengjia; Dong, Tiantian; Sun, Guochao; Liao, Ling; Deng, Qunxian; Wang, Xun; Zhu, Jin; Wang, Zhihui
Abstract : Methyl jasmonate (MeJA) is an airborne signaling phytohormone that can induce changes in endogenous jasmonates (JAs) and cause photosynthetic responses. However, the response of these two aspects of citrus plants at different MeJA concentrations is still unclear. Four MeJA concentrations were used in two citrus varieties, Huangguogan ( C. reticulata × C. sinensis ) and Shiranuhi [ C. reticulata × ( C. reticulata × C. sinensis )], to investigate the effects of MeJA dose on the endogenous JAs pathway and photosynthetic capacity. We observed that MeJA acted in a dose‐dependent manner, and its stimulation in citrus leaves showed a bidirectional character at different concentrations. This work demonstrates that MeJA at only a concentration of 2.2 mM or less contributed to the activation of magnesium protoporphyrin IX methyltransferase (ChlM, EC 2.1.1.11) and protochlorophyllide oxidoreductase (POR, EC 1.3.1.11) and the simultaneous accumulation of Chl a and Chl b, which in turn contributed to an improved photosynthetic capacity and PSII photochemistry efficiency of citrus. Meanwhile, the inhibition of endogenous JAs synthesis by exogenous MeJA was observed. This was achieved by reducing the ratio of monogalactosyl diacylglycerol (MGDG) to diagalactosyl diacylglycerol (DGDG) and inhibiting the activities of key enzymes in JAs synthesis, especially 12‐oxo‐phytodienoic acid reductase (OPR, EC 1.3.1.42). Another noteworthy finding is that there may exist a JA‐independent pathway that could regulate 12‐oxo‐phytodienoic acid (OPDA) synthesis. This study jointly analyzed the internal hormone regulation mechanism and the external physiological response, as well as revealed the effects of exogenous MeJA on promoting the photosynthesis and inhibiting the endogenous JAs synthesis.